Depressive symptoms and autonomic nervous system dysfunction in an elderly population-based study: The PROOF study - Dauphinot, Virginie; Rouch, Isabelle; Kossovsky, Michel P.; Pichot, Vincent; Dorey, Jean-Michel; Krolak-Salmon, Pierre; Laurent, Bernard; Roche, Frédéric; Barthélémy, Jean-Claude (Journal of affective disorders, 2012)
To assess the relationship between depressive symptoms, evaluated through self-reported history as well as current depressive symptoms, and impaired autonomic nervous system activity, evaluated by long-term heart rate variability and baroreflex sensitivity among elderly community residents, aged 65 years. Subjects from the Proof cohort Study were evaluated for depressive symptoms and self-reported history of depression at inclusion. Autonomic nervous system activity was assessed through 24-h heart rate variability and baroreflex sensitivity. Cross-sectional analyses were performed to study the relationship between the different status of depression and autonomic nervous system activity. Among the 1011 Proof study participants, 823 subjects were included in the analyses. Current depressive symptoms were present among 67 subjects; history of depression was reported by 228 subjects. Psychoactive drugs were used by 59 subjects. Low frequency (p=0.02), very low frequency (p<0.01) and Low/High frequency ratio (p<0.001) were lower among subjects with depressive symptoms and history of depression, independently of antidepressant treatment. The association remained significant for Low/High frequency ratio after adjustment for gender and physical activity (p=0.004). Current depressive symptoms may be linked to autonomic nervous system lower performances. A possible long-term effect of depressive symptoms at middle-age may influence later-life autonomic nervous system activity. Our results highlight the importance of taking into account the depressive symptoms in the cardiovascular risk, even in the elderly.